Perilaku Bullying pada Siswa SMA - Maria R. M. D. Longa; Sitti Anggraini (Mathematics Education Study Program, 2025)
The purpose of this study was to determine the description of bullying behavior in high school students. This study uses a quantitative descriptive research type. The population in this study were all students of SMA Negeri X totaling 1200 students. The sampling technique used non-probability sampling, namely purposive sampling. The criteria determined were grade XI students aged 15 to 18 years who had experienced bullying behavior. The sample in this study amounted to 285 people. This data collection technique used a bullying behavior scale based on Sejiwa's theory. The results of the study found that bullying behavior in students was categorized as high with a total of 225 people amounting to 78.94%, the moderate category amounting to 55 people amounting to 19.29%, and the low category amounting to 5 people amounting to 1.75%. Based on the results of the study, it was concluded that bullying behavior in grade XI students at SMA Negeri X was in the high category.